Poster 135: Minimum 2 year Clinical Outcomes after Latarjet for anterior shoulder instability: clinical and imaging factors that correlate with success or failure. Issue 7 (30th July 2022) - Millett, Peter; Provencher, Matthew; Casp, Aaron; Lee, Simon; Rakowski, Dylan; Peebles, Annalise; Ernat, Justin
Objectives: The open Latarjet procedure has been demonstrated to be reliable in achieving acceptable patient reported outcomes (PROs). However, clinical predictors of outcome, return to sport and complications/failures have been more variable. The purpose of this study is to report patient reported outcomes (PROs), clinical correlations, and predictors of failure in patients who have received an open Latarjet surgery. Methods: Patients who received an open Latarjet with by two fellowship–trained surgeons between August 2006 - November 2018 were included. Prospectively collected data was reviewed, and PROs included ASES, SF–12 PCS, SANE, QuickDASH, and satisfaction. Age, sex, sports participation, pain, primary vs. revision (prior failed arthroscopic/open Bankart) surgery, dislocation number, glenoid bone loss (GBL), glenoid track concept, and projected glenoid track were evaluated. Projected track was calculated using the axial diameter of the corcoid as part of the glenoid track concept. Postoperative ASES <70, recurrent dislocation, or revision instability surgery were considered failures. Results: 126 shoulders (125 patients) met inclusion criteria with mean age of 28.1 years (range 15–57). 7/126 (5.5%) had revision surgery prior to final follow-up and were excluded from outcomes analyses. Mean follow-up 3.7 years (range 2–9.3 years) was attained in 86.6% (103/119) of patients. All PROs significantly improved from preoperative baseline (ASES: 69.7→90.2; SANE: 55.8→85.9; QuickDASH: 28.4→10.5). PROs did not differ with sex, sport participation type, dislocation with/without sports, primary/revision, and preoperative dislocation number. No correlations existed between PROs and age, GBL, or number of previous surgeries. On-track (50/105, 47.6%) and projected on-track (90/105, 85.7%) lesions correlated with better patient satisfaction, but not PROs. A total of 97% (86/89) returned to sport, with 74% (66/89) at the same/slightly below pre-injury level. Failures included 13/126 (10.3%) postoperative dislocations and 6/126 (4.7%) with ASES scores <70. Conclusions: The open Latarjet procedure lead to significant improvements in all PROs, and overall 97% of patients returned to sport. On-track and projected on-track measurements correlated with better patient satisfaction, but not improved PROs. No other factors were predictive of outcomes, nor clinically correlated with failure.